2015
DOI: 10.5194/esd-6-591-2015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oceanic heat transport on the atmospheric circulation

Abstract: Abstract.A general circulation model of intermediate complexity with an idealized Earth-like aquaplanet setup is used to study the impact of changes in the oceanic heat transport on the global atmospheric circulation. Focus is on the atmospheric mean meridional circulation and global thermodynamic properties.The atmosphere counterbalances to a large extent the imposed changes in the oceanic heat transport, but, nonetheless, significant modifications to the atmospheric general circulation are found. Increasing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 65 publications
4
18
1
Order By: Relevance
“…Part of this modelled 410 N.Atlantic surface temperature underestimate may be due to a latitudinal temperature gradient being too high in the model (as also identified in previous modelling efforts of past warm climates), with heat transport to the poles being too low. Increased ocean heat transport was found to reduce the latitudinal temperature gradient and the location of Hadley and Ferrel cells in a modelling study by Knietzsch et al (2015), indicating the importance of atmospheric circulation, which in the cGENIE 2D energy-moisture balance atmosphere is simplified and invariant. The interaction between vegetation and atmosphere was found 415 to produce a warmer Miocene independent of CO2 by Knorr et al (2011).…”
Section: Climate Forcing and Co2 Levelsmentioning
confidence: 95%
“…Part of this modelled 410 N.Atlantic surface temperature underestimate may be due to a latitudinal temperature gradient being too high in the model (as also identified in previous modelling efforts of past warm climates), with heat transport to the poles being too low. Increased ocean heat transport was found to reduce the latitudinal temperature gradient and the location of Hadley and Ferrel cells in a modelling study by Knietzsch et al (2015), indicating the importance of atmospheric circulation, which in the cGENIE 2D energy-moisture balance atmosphere is simplified and invariant. The interaction between vegetation and atmosphere was found 415 to produce a warmer Miocene independent of CO2 by Knorr et al (2011).…”
Section: Climate Forcing and Co2 Levelsmentioning
confidence: 95%
“…Finally, the presence of larger temperature differences between high and low latitudes lead to a stronger atmospheric variability, as baroclinic conversion is more efficient and can draw from a larger reservoir of available potential energy. This is associated with a stronger Lorenz energy cycle compared to set-up A, see table 1; see a discussion of the climatic effects of modulating the meridional oceanic heat transport in the W state in [109].…”
Section: (B) Set-up B: Atmospheric-only Large-scale Energy Transport (I) the Three Competing Climate Statesmentioning
confidence: 99%
“…In addition, large-scale horizontal temperature gradients may play an important role in the global entropy budget. For instance, Knietzsch et al [2015] found decreases in frictional dissipation along with decreases in the pole-to-equator temperature gradient in GCM simulations in which the magnitude of a specified ocean heat transport was increased. In our study, moist convection is the focus, and large-scale motions and horizontal temperature gradients are not considered.…”
Section: Discussionmentioning
confidence: 99%